กลยุทธ์การตลาดคอนโดมิเนียมสำหรับกลุ่มวัยเริ่มทำงานของบริษัทพัฒนาอสังหาริมทรัพย์ :กรณีศึกษา บมจ. แสนสิริ บมจ. เอพี ไทยแลนด์ บมจ. พฤกษา เรียลเอสเตทและ บมจ. ออริจิ้น พร็อพเพอร์ตี้ - พราวนภา โกเมนธรรมโสภณ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
In the current world, the number of first jobbers tends to increase. However, there still exist limitations in terms of access to accommodation. Therefore, housing company entrepreneurs necessarily implement particular marketing strategies with this group of people. The current research endeavor aimed to study marketing strategies of condominiums for first jobbers adopted by Sansiri PCL, AP Thailand PCL, Pruksa Real Estate, and Origin Property PCL. The study adopted secondary data from the companies’ annual reports of 2021 and primary data from interviews of the owners of the four companies and first jobbers residing in the condominiums used in the study. Only one project from each company was chosen. There were 20 interviewees from each project from each of the companies. The total number of interviewees was 80. Similarities and differences of the marketing strategies were analyzed, along with condominiums chosen by first jobbers. A conclusion was drawn from the case studies.The results revealed that first, the companies chosen in the study considered first jobbers their major target group. This was specified in the company visions and responsibilities. Some of them demonstrated this notion in the executives’ concepts and competitive strategies. Moreover, important marketing strategies included allocation of market shares, and identification of target customers and locations. It was discovered that all of the companies were oriented towards affordability because the target customers were people of the new generation, working people, or GenZ people, who had specific standpoints in terms of prices, locations, characteristics of common areas, and room spaces. Some projects allowed pets. In addition, in terms of the marketing mix, most companies relied on online channels for distribution and adjusted common areas and rooms to respond to the needs of working people. Some of them welcomed new graduates and focused on working individuals as part of the project. Regarding condominium features chosen by working people, the locations of the condominiums were along the suburban areas, which were fully furnished and had plenty of storage spaces in the rooms. Also, the common areas were available 24 hours and equipped with spaces for meetings and exercising.The research results reflected the owners’ focus on working people and the important factor that brings about success for condominium owners aiming to attract working people is affordability and convenient locations for transportation which should be close to sky trains. The condominiums should also be fully furnished and ready to be used.